Growth and development of the Nigerian economy - Eicher, Carl K.; Liedholm, Carl ([East Lansing]: Michigan State University Press, 1970)
This volume analyzes the long-term growth process of the Nigerian economy from 1900 to independence in 1960, to review the performance of the economy in the 1960's and to focus on the leading economic policy issues of the 1970's.
Includes bibliographical references.
rua 28/02/2017
Loans.
Keywords: Economic growth; Economic development; Nigeria